THE INFLUENCE OF INSTAGRAM SOCIAL MEDIA USE, ENTREPRENEURSHIP LEARNING, AND LOCUS OF CONTROL ON INTEREST IN ONLINE ENTREPRENEURSHIP WITH SELF EFFICACY AS A MEDIATION VARIABLE - Zuwina Miraza; Eka Putri; Ilham Mubaraq Ritonga (RADJA PUBLIKA, 2025)
This research aims to determine the influence of the use of social media Instagram, entrepreneurial learning, and locus of control on interest in online entrepreneurship with self-efficacy as a mediating variable in students at the business economics faculty in Medan City, Stambuk University in 2018, 2019, and 2020. SmartPLS is used to test the relationship between constructs. The entire population used in this research was 200 respondents from the Faculty of Business Economics in Medan Stambuk City in 2018, 2019, and 2020 who had taken entrepreneurship courses. The results of the research show that the use of social media Instagram has no significant effect on self-efficacy and interest in online entrepreneurship, entrepreneurship learning has a significant effect on self-efficacy, entrepreneurship learning has no significant effect on interest in online entrepreneurship, locus of control has no significant effect on self-efficacy and interest in online entrepreneurship, Self-efficacy has a positive effect on interest in online entrepreneurship. The use of social media Instagram does not have a significant effect on interest in online entrepreneurship through self-efficacy. Entrepreneurship learning does not have a significant effect on interest in online entrepreneurship through self- efficacy. Self-efficacy has a significant effect on interest in online entrepreneurship through self-efficacy.